Incidence, characteristics and prognosis of different cardiac etiologies underlying cardiac syncope. (25th November 2020) - Lopez Ayala, P; Flores, D; Zimmermann, T; Du Fay De Lavallaz, J; Nestelberger, T; Strebel, I; Gualandro, D.M; Badertscher, P; Miro, O; Martin-Sanchez, F.J; Geigy, N; Christ, M; et al.
Abstract: Background: Cardiac syncope has been shown to carry the highest hazard for all-cause death compared to other causes of syncope including vasovagal and orthostatic syncope. However, little is known about the incidence, characteristics and prognosis of different cardiac etiologies underlying cardiac syncope. Purpose: To evaluate the incidence, characteristics and prognosis of different cardiac etiologies underlying cardiac syncope. Methods: We enrolled patients presenting to the emergency department (ED) with syncope in a large prospective international multicentre study. The cause of syncope (cardiac vs non-cardiac) including the detailed cardiac aetiology (if cardiac) was centrally adjudicated by two independent cardiologists based on detailed in-hospital as well as outpatient cardiac work-up during 360 days following presentation. Cardiac syncope was classified into four groups: bradyarrhythmia, tachyarrhythmia, structural disease and other (cardiopulmonary and great vessels), as recommended in the ESC Syncope Guidelines. All-cause death during 2-years follow-up was the primary outcome. Results: Among 2025 patients presenting with syncope to the ED, cardiac syncope was the final adjudicated diagnoses in 318 (15.7%) patients. The incidence rate of all-cause death among cardiac syncope patients was 103 cases per 1000 person-years. Bradyarrhythmia was the most frequent primary cause of cardiac syncope (n=146, 45.9%) followed by tachyarrhythmia (n=75, 23.6%), structural disease (n=64, 20.1%) and other cardiac (n=26, 8.2%). Patients were 37% female with a median age of 77 years (IQR 67–83) showing no statistically significant difference between subgroups. Clinical characteristics differed significantly among the four subgroups. E.g. syncope occurred during exercise in 12 patients (8.2%) with bradyarrhythmia, 10 patients (13.3%) with tachyarrhythmia, 16 patients (25%) with structural disease, and 5 patients (19%) with other cardiac (p<0.01). Likely of most importance, long-term mortality differed significantly among the four different cardiac subgroups. The multivariable-adjusted hazard ratios (HR) among patients with bradyarrhythmia, tachyarrhythmia, structural disease and other cardiac as compared to patients with vasovagal syncope, the HR were 1.3 (95% CI 0.7–2.5), 4.6 (95% CI 2.3–9.1), 3.1 (95% CI 1.5–6.4) and 5.9 (95% CI 2.3–15.2), respectively (Figure 1). Conclusions: Bradyarrhythmia, tachyarrhythmia, and structural cardiac disease are the dominant causes of cardiac syncope. Interestingly, with the appropriate therapy initiated long-term mortality of bradyarrhythmia is comparable to that of vasovagal syncope, while long-term mortality of tachyarrhythmia and structural cardiac disease were substantially increased 3 to 5 fold. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The Swiss National Science Foundation, the Swiss Heart Foundation, the Stiftung für kardiovaskuläre Forschung Basel, the University of Basel and the University Hospital Basel.